Biodegradation of 2,4-dichlorophenoxyacetic acid and 4-chlorophenol in contaminated soils by Pseudomonas fluorescens strain HH - Duc, Ha Danh; Oanh, Nguyen Thi; Hien, Nguyen Gia (Academia Journal of Biology, 2019)
Herbicides with 2,4-dichlorophenoxyacetic acid (2,4D) has been commonly used to control weeds and widely detected in environments. In this study, biodegradating activity of Pseudomonas fluorescens HH on 2,4D and 4-chlorophenol (4CP) in soil was carried out. The inoculation with Pseudomonas fluorescens HH in soils increased the degradation of 4CP and 2,4D by from 47.0% to 51.4% and from 38.4% to 47.4%, respectively, compared to the degradation by autochthonous microorganisms. Pseudomonas fluorescens HH could degrade well 2,4D and 4CP in various soils, but the most efficient chemical removal was observed when they were in the loamy soil. Moreover, the efficiency of chemical degradation was significantly affected by the moisture contents with the highest performance of degradation at 10 and 20% soil moisture. Also, the addition of nitrogen (N), phosphorous (P) and potassium (K) stimulated the dissipation rates. The determination of degradation pathway for 2,4D in Pseudomonas fluorescens HH indicated that 2,4-dichlorophenol (2,4DCP) and 4CP were formed as metabolites